Productivism and Post-Productivism: An Analysis of Functional Mixtures in Rural China - Yaofu Huang; Luan Chen; Xun Li (Land, 2022)
Existing studies have attempted to explain the transformation of rural China from a single productive or post-productive perspective. However, regarding the two development paradigms as binary opposites brings contradictions: Is China’s countryside evolving towards productivism or post-productivism? To answer this question, we transcend the binary opposition and instead propose an analytical framework based on rural value, driving actors, and rural land-use functions. Based on the location quotient analysis method, we measure the functional hybridity of rural areas using 7345 POIs (points of interest) representing the land-use types of productive and post-productive activities. We discuss the formation mechanism of functional hybridity considering two typical spaces: modern agriculture demonstration districts and “Tesecun”. We find that the government, the market, and villagers collectively promote the formation of functional hybridity in rural China. The government prefers to strengthen productivity in order to ensure state food security, while villagers prefer to make their villages more multi-functional in order to attract citizens. This study can be seen as a contribution supplementing research issues associated with rural China from the novel dualistic perspective of productivism and post-productivism.